An Adaptive Immune Algorithm based Gravimetric Fluid Dispensing Machine - Yap, David F. W. (Elseview, 2012)
A dispensing system is used in a materials-mixing plant to provide accurate blend ratios in producing the desired end-use product. The AIS-based (Artificial Immune Systems) fine tuning of dispensing parameters is proposed by optimizing the components of dispensing time and stopping time delay to obtain constant and accurate reading from the precision balance scale. Based on the new dispensing sequence, experimental tests had been carried out using different materials with varying viscosities. The results indicate that the combination of both PWM and AIS techniques would minimize overshoot while exhibiting lower steady-state error and faster response time. These are important in order to overcome the limitations of the conventional volumetric dispensing and manual parameter tuning presently applied in the dispensing system used in the coatings industry.